Impact of Healthcare Expenditures on Healthcare Outcomes in the Middle East and North Africa (MENA) Region: A Cross-Country Comparison, 1995–2015 - Balkhi, Bander; Alshayban, Dhfer; Alotaibi, Nawaf M. (Frontiers in Public Health, 2021)
Background: The association between healthcare expenditures and outcomes, mainly mortality and life expectancy, is complex. The real explanation for this association is not clear, especially in the Middle East and North Africa (MENA) region. Method: This study assesses the impact of health expenditures on improving healthcare systems and health status and finds a relationship between health expenditures and health outcomes. Annual time series data on healthcare spending and outcomes from 1995 to 2015 were used for 49 countries, both developed and developing. Health expenditure was adjusted by the consumer price index equation to the 2015 US dollar eliminate the impact of inflation on our results. Results: For many countries, spending on healthcare continues to rise, with the highest per-capita healthcare spending on healthcare in the United States, Norway, and Switzerland, with the highest spending ranging from $9200 to $9600 per capita. Among MENA countries, we found that the United Arab Emirates and Kuwait spent more per capita on health, $1711 and $1420, respectively, than any other countries in the region. Although this study demonstrated a relationship between total healthcare expenditure and outcomes, some countries spend more on healthcare but have shorter life expectancy. Conclusion: In most countries, efficient and effective utilization of healthcare resources is the key strategy for improving health outcomes in any country. The lack of a positive correlation between healthcare spending and life expectancy may indicate that health resources are not allocated effectively. In those cases, increasing health spending does not guarantee that there is any kind of improvement in healthcare.